Communication Behaviour of Women,Heading Farm Families in Neyyattinkara Taluk - Anitha Menon K (Department of Agricultural Extension, College of Agriculture, 1993)
A study on the Communication Behaviour of women heading farm families was carried out in five Krishibhavan areas under Neyyanttinkara taluk of Thiruvananthapuram district. Fifty women engaged in paddy cultivation and fifty from coconut cultivation formed the total sample of hundred respondents. The study was aimed to measure Communication Behaviour including Inward Exposure and Outward Exposure and to compare between the women cultivating paddy and the women cultivating coconut with regard to the dependent and independent variables of the study. It was also aimed to find the characteristics of women which influence Communication Behaviour, the relationship and the direct and indirect effects of these characteristics on Communication Behaviour. The data were collected using pre- tested structured interview schedule. The study revealed that the farm women in paddy cultivation had a high level of Inward Exposure. Women cultivating paddy were equally distributed in the low and high level of Outward Exposure categories and low level of Inward and Outward Exposure was noticed in majority of women cultivating coconut. The farm women had a low level of Communication Behaviour. Irrespective of the difference in the crop cultivated, the women did not differ significantly with regard to Inward Exposure, Outward Exposure, Communication Behaviour, and other selected characteristics. The characteristic profile study revealed that the respondents were middle aged and had a medium level of education (ie., upto high school) with a marginal farm size below 0.4ha. The women cultivating paddy had high level of social participation, cosmopoliteness, management orientation, scientific orientation, adoption of improved agricultural practices in paddy and knowledge about improved agricultural practices in paddy. With regard to women cultivating coconut, a medium level of social participation, high level of cosmopoliteness, scientific orientation, adoption of improved agricultural practices in coconut and a low level of management orientation were noticed. The women in coconut cultivation were distributed equally in the low and high level of knowledge about improved agricultural practices in coconut. The correlation co-efficients revealed that the selected characteristics of women were significantly correlated with Communication Behaviour and the correlation was positive except with the variable ‘age’. Path analysis results revealed that the maximum positive direct effect on Communication Behaviour was exerted by ‘knowledge about improved agricultural practices’ and ‘social participation’ with regard to women cultivating paddy and coconut respectively. The maximum positive indirect effect was exerted by ‘Adoption of improved agricultural practice’ and ‘knowledge about improved agricultural practices’ with regard to women cultivating paddy and coconut respectively.